Effects Of Mitragyna Speciosa Extracts On Drug Metabolizing Enzymes - Azizi, Juzaili (2011)
M. speciosa (ketum) leaves have been employed traditionally in Malaysia and Thailand to wean opium addiction and as a substitute for opium when opium is unavailable. M. speciosa leaves have been abused by drug addicts since some of the alkaloids (mainly mitragynine) from the plant possess opiate and cocaine like effects. These bring to its prohibition in Malaysia in 2004 since consumption of M. speciosa leaves has been perceived to lead to the abuse of other drugs such as cannabis and heroin. In the current study, the in vitro and in vivo effects of M. speciosa methanolic, aqueous and total alkaloid extracts on drug metabolizing enzymes, namely cytochrome P450 (CYP450), UDP-glucuronosyl transferase (UGT) and glutathione S-transferase (GST) had been evaluated in rat liver cytosolic fraction and microsomes.